Contribution of mobile phones in expanding human capabilities in selected rural districts of Tanzania. Issue 6 (2nd September 2019) - Msoffe, Grace E.P.; Lwoga, Edda Tandi
Abstract : Purpose: This study aims to investigate the use of mobile phones in enhancing human capabilities and agricultural development among small-scale farmers in selected rural districts of Tanzania. The study assessed the potential capabilities acquired by farmers, factors that influence farmers in building their capabilities and achieving development outcomes. Design/methodology/approach: The study used Sen's capability approach as a guiding framework to investigate the link between mobile phones and agricultural development. A case study design was employed whereby focus group discussions were used to collect data. Findings: The use of mobile phone services enabled rural farmers to build their financial, human and social capabilities. Rural farmers faced personal and non-personal conversion factors that influenced them in building capabilities and achieving development outcomes. The use of mobile phones led to various development outcomes. The typical development outcomes were related to access to information and communication services and reduction of transport costs. Rural farmers experienced family conflicts due to protectiveness exercised by couples through the use of mobile phones, criminal incidences such as theft and the fear of being recorded when making a phone call. Originality/value: The study findings have the potential of influencing policy and practice. The findings are useful in promoting the value of mobile phones usage in empowering rural farmers and communities. The telecommunication sector and other key stakeholders can use the study findings in setting the basis for prioritising the improvement of telecommunication infrastructure in the rural areas.